O cotidiano de Vitória nas páginas dos jornais A Gazeta e A Tribuna : práticas, comportamentos e modos de vida (1945-1955) - Paula, Alexandre Magno Vieira de (2013)
The main purpose of this work was to present the way the capixaba journals A Gazeta and A Tribuna used to report the facts, behavior and the daily ways of life in Vitória (ES.) from 1945 until 1955. In this study, the newspapers, as means of mediated communication, were taken by their importance and their capacity of influence in the social transformation processes. At that historical moment, the city of Vitória experienced several changes. So, the plans to economic growing and urban development based on the progress precepts, on the order and morality were widespread. Yet, in a certain degree, they were supported by both journals. Vitória was presented as “Cidade Presépio” due its natural beauty, and, at the same time, it was projected to be a regional and a port center with economic potential. As a result, some problems came due to the contradictions between a progress vision and the ‘Presépio”. Among them were the urban conflicts related, in general, to the lack of geographic space and incorrect occupation of some neighbourhoods. It was in that daily context within the capixaba capital that both journals, through their themes in the news and articles, worked as a kind of ruling instruments by seeking the control of practice, behavior, and ways of life that were seen as inappropriate to the set of customs and current moral values within the capixaba society. To reach their intent they claim in the journalistic pages for the urban (to the city) and moral (to their citzens) sanitation.